2011
DOI: 10.4161/bbug.2.3.15656
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting recombinant antibodies in point-of-care (POC) diagnostics: The combinatorial advantage

Abstract: Antibodies are ubiquitously deployed on in vitro diagnostic (IVD) platforms for detecting a panoply of analytes indicative of environmental and food contamination, residue adulteration and both veterinary and medical diagnostics. In the clinical realm, rapid and accurate determination of disease status is paramount. The significance of immunodiagnostic performance cannot be overemphasized and in many cases reliable diagnosis informs medical intervention which can mean the difference between patient recovery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The antibodies were generated from immunized repertoires by phage display and interacted with their cognate antigens with high affinity (scFv B8, 1 nM; scFv 180, 20 pM). These antibodies exemplify the power of display technologies, in particular phage display, to not only recapitulate (scFv B8) but also exceed (scFv 180) the diversity of host immune system to generate antibodies that surmount the theoretical affinity ceiling (8,49). Combinatorial libraries facilitate combinations of heavy and light chains that are truly randomized, not represented or accessible in the natural B-cell repertoire, and routinely permit isolation of antibodies with sub-single digit nanomolar affinities (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The antibodies were generated from immunized repertoires by phage display and interacted with their cognate antigens with high affinity (scFv B8, 1 nM; scFv 180, 20 pM). These antibodies exemplify the power of display technologies, in particular phage display, to not only recapitulate (scFv B8) but also exceed (scFv 180) the diversity of host immune system to generate antibodies that surmount the theoretical affinity ceiling (8,49). Combinatorial libraries facilitate combinations of heavy and light chains that are truly randomized, not represented or accessible in the natural B-cell repertoire, and routinely permit isolation of antibodies with sub-single digit nanomolar affinities (8).…”
Section: Discussionmentioning
confidence: 99%
“…The natural immune repertoire is dynamic, with the capacity to generate a repertoire of 10 8 by affinity maturation in vivo, which is substantiated by continual exposure or sensitization to antigens from the environment or by immunization (8). Artificial manipulation of antibody genes has facilitated in vitro selection of truly unique antibodies from extremely large combinatorial libraries, which can be constructed from virtually any species, isolated from B-cells derived from naïve, immunized, or infected subjects or are partially or wholly synthesized in vitro (8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant antibodies are produced by exploiting genetic techniques to generate a variety of antibody constructs, such as Fab (fragment antigen binding) Abs and scFv (single-chain fragment variable) Abs [44]. The production method used here offers considerable advantages, such as the Ab size being smaller, enabling a greater density of Abs to be immobilised, and the capacity to add tags to enhance immobilisation and ensure correct orientation [45,46]. A study comparing the use of Ab fragments has shown that their incorporation into an assay may reduce the interference from matrix biomolecules, in addition to reducing reagent consumption and increasing the assay sensitivity [47].…”
Section: Biomarker Recognitionmentioning
confidence: 99%